2023
DOI: 10.1002/cbdv.202200915
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Polyphenol Contents and Biological Activities of Five Cistus L. Species Native to Turkey

Abstract: In this study phytochemical compounds and antioxidant capacity, cytotoxic, antimicrobial and anti-biofilm activities of hydroethanolic extracts of five Cistus species (C. creticus L., C. laurifolius L., C. monspeliensis L., C. parviflorus Lam. and C. salviifolius L.) distributed in Turkey were investigated. (+)-catechin, epigallocatechin gallate, quercetin-3-O-rutinoside, quercetin-3-O-glucoside, kaempferol-3-O-glucoside, luteolin were detected in different amounts. Strongest antioxidant capacities were observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…The analysis also revealed the presence of epigallocatechin gallate, luteolin, quercetin-3-glucoside, and catechin in the extract of C. parviflorus at concentrations of 5.78, 15.21, 0.84, and 5.35, respectively . The findings of the study by Onal et al demonstrated the plant’s biogenetic capacity to synthesize various flavonoids and demonstrated that C.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The analysis also revealed the presence of epigallocatechin gallate, luteolin, quercetin-3-glucoside, and catechin in the extract of C. parviflorus at concentrations of 5.78, 15.21, 0.84, and 5.35, respectively . The findings of the study by Onal et al demonstrated the plant’s biogenetic capacity to synthesize various flavonoids and demonstrated that C.…”
Section: Resultsmentioning
confidence: 92%
“…In addition, they have detected kaempferol-3-glucoside only in C. criticus . The analysis also revealed the presence of epigallocatechin gallate, luteolin, quercetin-3-glucoside, and catechin in the extract of C.…”
Section: Resultsmentioning
confidence: 95%
“…Moreover, Álvarez-Martínez et al [ 35 ] investigated the activity of C. salviifolius against 100 S. aureus clinical isolates and referred MIC 50 values ranging between 50–80 μg/mL. The authors also documented that the Cistus extracts containing hydrolysable tannins and flavonoids such as myricetin and quercetin derivatives showed the higher activity against MRSA isolates.Among the Cistus extracts, C. laurifolius exhibited antibacterial efficacy against S. aureus and E. coli [ 36 ] and inhibitory activity against microbial biofilm production [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hydroethanolic extracts of numerous plants have been reported to significantly reduce the S. aureus biofilm formation, which could be explained by the presence of chlorogenic, quercetin, and rutin [ [111] , [112] , [113] ]. Likewise, due to rich and diverse phytochemical compositions, the methanolic extract of Capsicum annuum at 64 μg/mL showed an inhibition rate of 53.8 % against S. aureus biofilm, comparable to amoxicillin [ 114 ].…”
Section: Emerging Natural Products-based Therapeutics Against ...mentioning
confidence: 99%